Structure identification and toxicity evaluation of one newly-discovered dechlorinated photoproducts of chlorpyrifos. (August 2022) - Jiang, Feng; Wu, Wanqin; Zhu, Zhengwei; Zhu, Songsong; Wang, Huixia; Zhang, Li; Fan, Zhiyong; Chen, Yiping
Abstract: Chlorpyrifos (CPF) is an extensively used organophosphorus pesticide. Recently, it has attracted increasing attention due to environmental health problems caused by it. Although numerous studies have discovered the dechlorinated photoproduct of CPF, its structure and toxicity remain largely unknown. In this study, we systematically investigated the structure and toxicity of dechlorinated photoproduct of CPF. The CPF degradation experiment was performed, and its products were identified by ultra high performance liquid chromatography-orbitrap fusion tribid mass spectrometer (UHPLC-Orbitrap Fusion TMS). Additionally, bond dissociation energy (BDE) calculations and photoproduct chemical synthesis were employed to determine the structure of dechlorinated photoproduct of CPF. The toxicity of CPF photoproduct was evaluated through the Ecological Structure Activity Relationships (ECOSAR) Class Program, the Toxicity Estimation Software Tool (T.E.S.T.) software, and acute toxicity testing. The results indicated that the dechlorinated photoproduct of CPF was identified as O, O-Diethyl-O-(3, 5-dichloro-2-pyridyl) phosphorothioate (Dechloro-CPF), which was produced in large quantity within the first 30 min of photodegradation experiment. The acute and chronic toxicity values of Dechloro-CPF were obviously higher than those for the other two photoproducts. The median lethal dose (LD50 ) of Dechloro-CPF was 31.6 mg/kg for female mice and 58.4 mg/kg for male mice. This study reveals the photodegradation mechanism of CPF and confirms that Dechloro-CPF was dechlorinated photoproduct of CPF with potential acute toxicity to aquatic species and mammalian (including human). Our findings will contribute to a more comprehensive risk evaluation of CPF in food and the environment. Graphical abstract: Image 1 Highlights: The dechlorinated photoproduct was generated in photolysis experiments of Chlorpyrifos. The dechlorinated photoproduct of Chlorpyrifos was O, O-Diethyl-O-(3, 5-dichloro-2-pyridyl) phosphorothioate (Dechloro-CPF). The toxicity of Dechloro-CPF photoproduct was assessed.